Gender difference in suicidal ideation and related factors among rural elderly: a cross-sectional study in Shandong, China - Lu, Lu (Ann Gen Psychiatry, 2020)
BACKGROUND: Suicide is a global public health problem which has significant negative influence on individuals, families and the society. The aim of this study is to investigate the prevalence of suicidal ideation and related factors among elderly people in rural China, and further examine the gender differences of suicidal ideation. METHODS: Data were collected from the 2017 Survey of the Shandong Elderly Family Health Service, which was conducted by Shandong University. A total of 5514 elderly aged 60 and above from rural Shandong were included in this study. Binary logistic regression model was performed to examine the gender difference towards suicidal ideation, and to identify the influencing factors of suicidal ideation by gender among elderly. RESULTS: 7.7% rural elderly reported suicidal ideation in the past 12 months in Shandong, China. The prevalence of suicidal ideation among females was significantly higher than that among males (P < 0.001). Education level, debts, stress of daily life, loneliness and psychological distress were significantly related to suicidal ideation in both males and females. Besides, negative life events and life satisfaction were found to be significantly associated with suicidal ideation in females but not in males. CONCLUSIONS: There was a significant gender difference towards suicidal ideation among rural elderly in Shandong, China. So, gender difference should be considered when medical practitioners and public health workers seek to prevent and manage suicidal ideation among rural elderly, which will be important to develop strategies for coping with risk factors for suicidal ideation among males and females. In other words, more attention should be paid to females who had encountered negative life event or with lower life satisfaction.